Evaluation of residual tumors and recurrence rates of malignant melanoma and non-melanoma skin cancer of head and neck region - SAÇAK, BÜLENT; DURMUŞ KOCAASLAN, FATMA NİHAL; ÇELEBİLER, ÖZHAN BEKİR (MARMARA UNIV, FAC MEDICINE, 2019)
Objective: In this study, we aimed to evaluate residual tumors and recurrence rates of malignant melanoma (MM) and a nonmelanoma skin cancer of (NMSC) head and neck region. Patients and Methods: Medical data of a total of 398 lesions of 323 patients who underwent surgical excision for a basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and malignant melanoma (MM) were retrospectively analyzed. All patients were classified according to age, sex, location of the tumor, histopathological diagnosis, lesion diameter, excision diameter, surgical margin status, and residual lesions and recurrence rates. Results: There were 244 lesions (61.3%) in 189 males and 154 lesions (38.7%) in 134 females. The most common type of skin cancer was BCC in 268 lesions (67%), followed by SCC in 122 (31%), and MM in eight (2%), respectively. Recurrence was seen in 3% of the NMSC cases and in 25% of the MM cases. There was a statistically significant correlation between the histopathological diagnosis and recurrence rates. Compared to NMSC, MM cases had a higher risk for recurrence (p=0.029). Conclusion: Our study results suggest that recurrence is associated with the localization and type of the tumor, but not with the age or sex of the patient.
Keywords: Basal cell carcinoma; Squamous cell carcinoma; Malignant melanoma; Recurrence; Residual tumor; BASAL-CELL CARCINOMA; INCOMPLETE EXCISION; SURGICAL-TREATMENT; EPIDEMIOLOGY; MARGINS; AGE